Assessment of the relationship between the presence of these disorders and health-related quality of life, functional capacity and use of health services. - Sousa, Lis Rejane de; Rodrigues, Janaina Damascena; Sousa, Amanda Antunes de; Rodrigues, Isabella Fernandes; Santos, Franklin; Ferreira, Cristiane Martins (Brazilian Journal of Implantology and Health Sciences, 2025)
Introduction: Anxiety and depression disorders are highly prevalent mental health conditions with profound global impact. Their clinical manifestations are not restricted to the sphere of psychological distress, but have widespread repercussions in multiple domains of an individual’s life. These disorders are often associated with deterioration in physical health, impairment of social relationships, and significant loss of work and personal productivity. This complex interaction between mental health and general well-being has justified in-depth investigation of their direct consequences on the perception of health and the patient’s interaction with the health care system. Objective: The objective of this systematic review was to analyze and synthesize the available scientific evidence on the association between the presence of anxiety and depression disorders and health-related quality of life, functional capacity, and patterns of use of health services in adult populations. Methodology: A systematic review of the literature was conducted, based on the PRISMA checklist guidelines, with articles published in the last 10 years. The searches were performed in the PubMed, Scielo and Web of Science databases, using the following descriptors and their combinations: "depression", "anxiety", "quality of life", "functional capacity" and "use of health services". The inclusion criteria were: observational studies (cross-sectional or cohort), samples composed of adults and evaluation of at least one of the outcomes of interest. Review studies, clinical trials that evaluated specific interventions and research focused exclusively on pediatric populations were excluded. Results: The results found in the analyzed studies consistently demonstrated a strong negative association between the presence of anxiety and depression disorders and the evaluated outcomes. Individuals with these diagnoses presented significantly lower scores in all domains of health-related quality of life. Furthermore, a higher prevalence of functional disability was observed, with reports of greater difficulty in performing activities of daily living and greater absenteeism at work. The pattern of health service utilization was more intense in this group, characterized by a greater number of medical consultations, a greater frequency of emergency room visits, and higher hospitalization rates. Conclusion: Anxiety and depression disorders were found to be conditions that imposed a substantial burden, extending far beyond emotional symptoms. The presence of these disorders was directly associated with a marked worsening of quality of life, a significant decline in functional capacity, and a burden on health systems. These findings reinforce the need for integrated care approaches that recognize and address the multifaceted impact of mental health on the overall well-being of the patient.